Co-management of the Porcupine Caribou Herd - Peter, Albert; Urquhart, Doug (Rangifer, 1996)
The success of a co-management organization rests with the user communities. Over the years members of the Porcupine Caribou Management Board have observed that it is the knowledge and concerns held by the people in the communities which are affected by caribou management policies, that provide the greatest inspiration to the Board. In return, the Board must never lose sight of its primary objective which is to manage and conserve the Porcupine Caribou Herd by incorporating native participation at every level of decision-making.